Analytical Description of Non-Nursing Task Performed by Nurses in Hospital of Baubau City - Safar, Ade; Rachmawaty, Rini; Andriani, Andriani (Faculty of Nursing, Universitas Hasanuddin, 2022)
Introduction: Outside of nursing actions that are carried out in accordance with the professionalism of the nursing profession, there are actions that are carried out outside the realm of the nursing profession known as non-nursing task. Non-nursing measures have been shown to increase the risk of missed or delayed nursing care. The purpose of this study was to describe non-nursing task performed by nurses in the Baubau City General Hospital. Method: This research is a quantitative research using descriptive analytical survey analysis method which is used to describe the phenomena or events that are analyzed according to the data in one measurement without giving special treatment to the phenomenon to 85 respondents. The sampling method in this study used a purposive sampling technique. Result: Cleaning the patient's room and equipment is the most frequent non-nursing task by respondents with 33 respondents (38.8%) answering often and routine blood sampling for tests as many as 32 (37.6%) respondents stating often, while the act of providing care outside the scope of nursing, there were 5 respondents answered